A novel BMPR2 mutation with widely disparate heritable pulmonary arterial hypertension clinical phenotype. (1st June 2020) - Oriaku, Ifeoma; LeSieur, Mallory N.; Nichols, William C.; Barrios, Roberto; Elliott, C. Gregory; Frost, Adaani
Abstract : Mutations in the gene encoding bone morphogenetic protein receptor type II ( BMPR2 ) have been associated with heritable pulmonary arterial hypertension (HPAH), whereas mutations in the gene encoding eukaryotic translation initiation factor 2 alpha kinase 4 ( EIF2AK4 ) are associated with heritable pulmonary veno‐occlusive disease/pulmonary capillary hemangiomatosis (HPVOD/PCH). We describe two unrelated patients found to carry the same hitherto unreported pathogenic BMPR2 mutation; one of whom presented with typical pulmonary arterial hypertension, whereas the second patient presented with aggressive disease and characteristic clinical features of PVOD/PCH. These two clinically divergent cases representative of the same novel pathogenic mutation exemplify the variable phenotype of HPAH and the variable involvement of venules and capillaries in the pathology of the pulmonary vascular bed in pulmonary arterial hypertension.